Effectiveness of music therapy in children with autism spectrum disorder: A systematic review and meta-analysis - Ke, Xiaohua; Song, Wei; Yang, Minguang; Li, Jianhong; Liu, Weilin (Frontiers in Psychiatry, 2022)
Objectives This study was to investigated the efficacy of music therapy (MT) in children with autism spectrum disorder (ASD) via a meta-analysis that comprehensively evaluated data from all eligible research in this field. Design Systematic review and meta-analysis. Setting A systematic search of the PubMed, Embase, and Cochrane Library databases from inception to October 2021 to identify studies that administered MT to children with ASD. Results Eight randomized controlled trials (RCTs) including 608 participants met the inclusion criteria. The meta-analysis showed that MT was associated with a significant increase in social reactions among children with ASD (standardized mean difference (SMD) = 0.24, 95% confidence interval (CI) [0.03, 0.46], I2 = 0%, P = 0.03). However, MT did not elicit a significant increase in symptom severity (SMD = 0.17, 95% CI [−0.04,0.38], I2 = 0%,P = 0.12), social adaptive behavior (SMD = 0.02, 95% CI [−0.44,0.48], I2 = 0%,P = 0.93) or speech (SMD = 0.04, 95% CI [−0.39, 0.47], I2 = 0%, P = 0.86) in children with ASD. Conclusion MT can improve social skills in children with ASD; however, there does not seem to be a consensus on the persistence of its effects. These findings can inform clinical practice. Promoting the use of MT in children with ASD and improving its symptoms are the ultimate goals.